2011
DOI: 10.1161/hypertensionaha.111.173799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Renal Sympathetic Denervation on Blood Pressure, Sleep Apnea Course, and Glycemic Control in Patients With Resistant Hypertension and Sleep Apnea

Abstract: Abstract-Percutaneous renal sympathetic denervation by radiofrequency energy has been reported to reduce blood pressure (BP) by the reduction of renal sympathetic efferent and afferent signaling. We evaluated the effects of this procedure on BP and sleep apnea severity in patients with resistant hypertension and sleep apnea. We studied 10 patients with refractory hypertension and sleep apnea (7 men and 3 women; median age: 49.5 years) who underwent renal denervation and completed 3-month and 6-month follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
269
1
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(304 citation statements)
references
References 28 publications
13
269
1
14
Order By: Relevance
“…Subgroup analysis and phase II testing have also shown improvements in other diseases associated with autonomic dysfunction, such as sleep apnea, insulin-resistant diabetes, left ventricular (LV) hypertrophy, tachyarrhythmias, and congestive heart failure (CHF) (13,16). Ongoing RDN clinical trials for the treatment of resistant HTN continue this trend of investigating other potential benefits associated with RDN.…”
Section: Current Clinical Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subgroup analysis and phase II testing have also shown improvements in other diseases associated with autonomic dysfunction, such as sleep apnea, insulin-resistant diabetes, left ventricular (LV) hypertrophy, tachyarrhythmias, and congestive heart failure (CHF) (13,16). Ongoing RDN clinical trials for the treatment of resistant HTN continue this trend of investigating other potential benefits associated with RDN.…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…Witkowski et al (16) showed that OSA was a consequence as well as a cause of increased sympathetic activity in patients who underwent RDN for resistant HTN. These investigators also reported that the apneahypopnea index improved in 8 of 10 patients 6 months after RDN.…”
Section: Application Of Rdn In Osamentioning
confidence: 99%
See 2 more Smart Citations
“…These findings emphasize the importance of autonomic imbalance in OSA-associated AF. Also, renal sympathetic denervation (RDN) has also been shown to reduce OSA-severity in hypertensive patients as well as blood pressure (Witkowski et al 2011).…”
mentioning
confidence: 99%